Corporate Business Strategy and Tax Avoidance Culture: Moderating Role of Gender Diversity in an Emerging Economy - Xiaochen Zhang; Xiaochen Zhang; Muhammad Husnain; Hailan Yang; Saif Ullah; Jaffar Abbas; Jaffar Abbas; Ruilian Zhang (Frontiers in Psychology, 2022)
Tax payments stimulate business enterprises to choose tax management through tax avoidance activities, which is the legal practice to reduce the amount of tax payable. In developing economies, taxation is considered more critical for budget and revenues of a country. This paper investigates whether various business strategies influence corporate tax avoidance decisions of firms by adopting business strategies. Besides, it explores how gender diversity can ease this relationship. This study has chosen a sample of organizations from non-financial sector in Pakistan. The time frame is 5 years, including once a year. The present model employed a generalized moment method (GMM) and tested the proposed hypothesis to draw the results. The study has taken the size, leverage, and business profitability as control variables of firms. The study outcomes by using the GMM method demonstrate that the presence of female directors reduces tax avoidance behavior in prospector companies. This study provides insight into future research for stakeholders, government officials, tax authorities, and policymakers. The findings offer valuable recommendations and practical insights and implications. The findings provide future directions for research to test different frameworks to attain beneficial results to promote the responsibility of tax payment culture.